Listening to the murmur of water: Essential satisfaction and dissatisfaction attributes of thermal and mineral spas - Rodrigues, H. (2020)
Thermal and mineral spa treatments are an important therapeutic tool backed by centuries of experience and numerous scientific studies showing its effectiveness. The research consisted of content analysis of 1,254 customer reviews posted online from 2015 to 2019. Qualitative analysis identified five key themes: thermal (spa), staff, room, location, and pool. On a theoretical level, this research’s results help to fill research gaps in the literature by separating attributes linked to satisfaction from those related to dissatisfaction. This study is different as we focus on the factors affecting tourism satisfaction and dissatisfaction in thermal and mineral spas using sentiment analysis.